2020
DOI: 10.1186/s12991-020-00310-6
|View full text |Cite
|
Sign up to set email alerts
|

The association of intimate partner violence with postpartum depression in women during their first month period of giving delivery in health centers at Dessie town, 2019

Abstract: Background Postpartum depression is a common psychiatric complaint of women following delivery and a multitude of psychosocial, maternal, newborn and husband-related factors were contributing to it. This condition has a detrimental impact on the mother–infant caregiving relationship and hastens the infant’s cognitive, emotional and social development. However, a shortage of empirical evidence existed especially in developing countries including Ethiopia. Therefore, we implemented this study to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 66 publications
(112 reference statements)
2
1
0
Order By: Relevance
“…Participants in the present study characterized IPV as aggressive behavior with various types of abuse such as verbal attacks, physical assault, sexual violence, neglect and victimization. The findings of the present study are in tandem with observations of other studies from Africa and other low-income countries [ 10 , 41 ]. In a number of studies, alcoholism and substance abuse has been reported as a key trigger of IPV during the postpartum period [ 11 , 41 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Participants in the present study characterized IPV as aggressive behavior with various types of abuse such as verbal attacks, physical assault, sexual violence, neglect and victimization. The findings of the present study are in tandem with observations of other studies from Africa and other low-income countries [ 10 , 41 ]. In a number of studies, alcoholism and substance abuse has been reported as a key trigger of IPV during the postpartum period [ 11 , 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…The findings of the present study are in tandem with observations of other studies from Africa and other low-income countries [ 10 , 41 ]. In a number of studies, alcoholism and substance abuse has been reported as a key trigger of IPV during the postpartum period [ 11 , 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…Same findings have been made among pregnant women in Jos, North-Central Nigeria [5]. Ethiopian researchers have reported that being single was the first socio-demographic variable associated with PPD and that single mothers were 5 times more likely to develop PPD than the married mothers [12]. Marriage in the African context makes a woman to be more acceptable and respectable and therefore having a baby the "legitimate way" boosts their self-esteem and gives them a perception of increased worth both within their homes and the wider society.…”
Section: Discussionmentioning
confidence: 58%
“…This is in keeping with report that physical and verbal abuse increased the risk of PPD by 18-fold and 7-fold respectively. [9] In addition, Ethiopian researchers reported higher odds of developing PPD among women who had experienced psychological and physical abuse [12].…”
Section: Discussionmentioning
confidence: 99%
“…Postpartum depression (PPD) is a long‐lasting mood disorder that occurs within the first month after childbirth (American Psychiatric Association, 2013). PPD affects approximately 10.3% to 27.0% of mothers in the first month (Necho et al, 2020; Sylven et al, 2016). In Asia, a wide range of PPD prevalence ranging from 3.5% to 63.3% has been reported (Klainin & Arthur, 2009), and cultural traditions are assumed to contribute to this discrepancy (Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%